Fortifikasi Antioksidan Beras Analog Kombinasi Ubi Jalar (Ipomoea batatas L.) dan Kelor (Moringa oleifera) sebagai Upaya Diversifikasi Pangan Penderita Diabetes Melitus - Putra Nugraha, I Made Arie Dharma; Dwidhananta, I Made Sasmita; Dewi, Ni Kadek Diah Parwati; Gelgel Wirasuta, I Made Agus (Jurnal Farmasi Udayana; Vol. 10, No 1, Tahun 2021, 2021)
Introduction: Diabetes mellitus (DM) is classified as a silent killer in society. Insulin therapy is generally the management of DM, morever there is a side effect of weight gain from hypoglicemic effects. Another solution is a low glycemic index food diet in analogue rice form. The materials constructed as analogue rice are sweet potato tubers (Ipomoea batatas L.), with high dietary fiber and low glycemic index, as well as antioxidant fortification of Moringa oleifera leaves. Objectives: Updating the latest knowledge on the chemical composition of raw materials and health benefits for people with diabetes, along with analogue rice making technology in order to get the best results. Methods: This study was conducted with a literature review method which is classified as a systematic qualitative descriptive study. Results: Various studies have shown that both raw materials are reported to have various chemical compounds and nutritional components, low glycemic index, antioxidant activity, and anti-DM. Hot extrusion technology provides the best results in making analogue rice. Conclusion: The analogue rice production made from sweet potato tubers and antioxidant fortification of moringa leaves by hot extrusion are used to produce functional herbal products as a result to diversify the food for DM sufferers. Keywords: Ipomoea batatas L., Moringa oleifera , analog rice, fortification, and diabetes mellitus